Uncertainty analysis on progressive collapse of RC frame structures under dynamic column removal scenarios. (1st April 2022) - Lin, Kaiqi; Chen, Zefan; Li, Yi; Lu, Xinzheng
Abstract: The progressive collapse of structures often causes serious casualties and property loss. The intrinsic characteristic of progressive collapse is large-scale domino-like structural damage caused by accidental local failure induced by uncertainty factors. Therefore, it is vital to conduct uncertainty analyses on the progressive collapse of reinforced concrete (RC) frame structures under dynamic loads. In this study, to better quantify the progressive collapse resistance of RC frame structures, progressive collapse fragility analyses and sensitivity analyses were conducted at both the component and structural levels, taking into consideration the uncertainties in the structural design parameters, including structural loads, geometries, material properties, etc. At the component level, an energy-based simplified analysis method was proposed for the quick assessment of the progressive collapse vulnerability of RC beam-column substructures. At the structural level, a fragility curve cluster was adopted for evaluating the progressive collapse resistance of RC frame structures. A typical 3-story, 4 × 3 span RC frame structure designed according to Chinese codes was evaluated by the progressive collapse fragility curve cluster. It is found that the failure probability of the RC frame may increase by more than 30% after considering the uncertainty factors. Based on the fragility curve cluster, the robustness and reliability of both the RC frame and its components were quantified. And a safety index is proposed for judging whether a structure/component requires a progressive collapse redesign. Furthermore, the sensitivity analysis results indicate that the load effects, strength of the reinforcement steel, and the reinforcement area in a beam significantly affect the structural progressive collapse resistance. The research outcomes can provide references for quantifying the progressive collapse resistance and improving the progressive collapse design of RC frame structures. Highlights: ● The progressive collapse resistance of RC frame structures is investigated. ● Both uncertainty and sensitivity analyses of the modeling parameters are conducted. ● A simplified fragility assessment method for RC substructures is proposed. ● A fragility curve cluster is proposed for evaluating the resistance of an RC frame. ● The reliability of an RC frame against progressive collapse is quantified.